ANALISIS KETERAMPILAN METAKOGNITIF DAN SIKAP ILMIAH SISWA MELALUI METODE PEMBELAJARAN INKUIRI - Suriani Siregar (Universitas Islam Negeri Ar-Raniry, 2019)
This research is a descriptive study with the aim to analyze metacognitive skills and scientific attitudes of biology students on Genetic materials through inquiry learning models. This research was carried out in Universitas Gunung Leuser Aceh. The sample in this study is Biology students in semester VI totaled 24 students. Data on the ability of metacognitive skills were obtained by questionnaire while scientific attitude data were obtained by observation sheets. Data were analyzed with descriptive analysis techniques. The results is that the metacognitive skills of students is in the very good category (80,50%) while the students’ scientific attitude is in the good category (72,29%). The result shows that the inquiry learning models can improve biology students’ metacognitive abilities and scientific attitudes on Genetic materials.